The power to change mastering the habits that matter most - Craig Groeschel (Zondervan Grand Rapids, 2023)
"Craig Groeschel knows what it's like to be caught in the dispiriting cycle of trying to change, but failing. This was his story--until he began to discover practical principles for experiencing lasting change in his own life that he has taught to countless others for over twenty-five-plus years at LifeChurch"-- Provided by publisher.
Keywords: Change (Psychology)--Religious aspects--Christianity.